Experimental and numerical investigations on dynamic mechanical responses and failure process of gas-bearing coal under impact load - Kong, Xiangguo; Li, Shugang; Wang, Enyuan; Wang, Xu; Zhou, Yuxuan; Ji, Pengfei; Shuang, Haiqing; Li, Shaorong; Wei, Zongyong (Soil dynamics and earthquake engineering (1984), 2021)
With mining depth increasing, the mining structure becomes more and more complex. It is easy to cause dynamic disaster during coal mining. To reveal the failure process of gas-bearing coal at complex mining environment, the dynamics experiments were conducted through Split Hopkinson Pressure Bar of gas-bearing coal (SHPB-GAS) experimental system. The results showed that the filtered stress waveform presented to be sine-like. With the impact load increasing, the amplitude of incident wave, reflected wave and transmission wave also increased. After calculation of stress wave data, the stress-strain curves were obtained, which included linear elastic stage, step stage, yield and rupture stage. The dynamic mechanical strength increased with the increase of impact load, and the specimen developed from stratiform rupture with macro cracks to crush rupture in fragments. To verify the experimental results, COMSOL Multiphysics software was adopted to conduct numerical simulation. The simulation results indicated that the high stress area was formed at the end faces of specimen firstly and expanded to interior of specimen gradually under different impact load. High stress induced the plastic deformation in coal specimen, which also developed from end faces to specimen inside. These results were consistent with the phenomenon of experiments, which explained the causes of failure process of gas-bearing coal. Based on the experimental and simulation achievements, the formed mechanism of dynamic disaster induced by impact load were discussed. •Stress waveform, stress-strain and failure process of gas-bearing coal were researched.•Stress distribution and plastic deformation ware discussed in numerical simulation.•Dynamic disaster of gas-bearing coal in coal mine was discussed.